(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The aim of the study was to determine the effectiveness of a biologically-based system for optimizing the nutrition of beetroot mother roots under strip placement of vegetable crops and legume–cereal mixtures (Rot–Mix system) in the soil and climatic conditions of the Left-Bank Forest-Steppe of Ukraine. Field experiments were conducted on chernozem soils at the Institute of Vegetable and Melon Growing of the National Academy of Agrarian Sciences of Ukraine using beetroot varieties of different typologies (Bordo Kharkivskyi, Vital, Bahrianyi) and biological products of various functional groups to optimize plant nutrition, stimulate growth processes, and protect against harmful organisms (Azotofit-R, Organic-Balance, Groundfix, Humifrend, HelpRost for vegetable crops, HelpRost Boron, Micohelp, Phytohelp, Aktovirm Formula, Liposam). The impact of the biologically-based fertilization system on the yield and output of beetroot mother roots of different varieties, as well as the main economic indicators of the cultivation technology, was determined. It was established that the biologically-based fertilization system statistically significantly increased the yield of beetroot mother roots by 5.7–7.8 t/ha, or 15.3–24.5 %, compared to the baseline technology. The highest yield over the years of the study was recorded for the Vital variety, and the lowest for the Bahrianyi variety. The biologically-based fertilization system ensured a positive trend in increasing the proportion of mother roots to 52.5 % compared to the baseline technology (48.8 %). The implementation of the biologically-based fertilization system resulted in an increase in net profit, depending on the variety, by 28.5–39.0 thousand UAH/ha, a reduction in production costs to 2.80–3.53 UAH/kg, and an increase in profitability to 60.3–90.3 % compared to the baseline technology for cultivating beetroot mother roots. The application of these technological approaches will ensure the future production of vegetable seeds suitable for organic cultivation technologies.